Ant Financial : flourishing farmer loans at MYbank - Xu, Jingyue (SAGE Knowledge. Cases., 2017)
In 2015, Ant Financial's MYbank (an offshoot of Jack Ma's Alibaba company) was looking to extend services to rural areas in China through its Flourishing Farmer Loan program. MYbank relied on the internet to communicate with loan applicants and judge their credit worthiness. Initial tests of the program had proved promising, but could MYbank operate the program at scale? Would its big data and technical analysis provide an accurate measure of credit risk for loans to small customers? Could MYbank rely on its new credit-scoring system to reduce operating costs to make the program sustainable?